Increase of compliance of chronic patients as aspects of pharmaceutical care - I A Kirschina; A V Soloninina; A D Katkova (RUDN Journal of Medicine, 2013)
The paper presents the importance of the problem of insufficient patient complains of chronic diseases and the results of the analysis on the example of noncompliance in patients with diabetes mellitus. The basic reasons for the low noncompliance with chronic diseases, the necessity and possibility of participation of pharmaceutical professionals to improve adherence to treatment of patients with chronic diseases (for example, diabetes).